Sequence and secondary structure of the colicin fragment of Bacillus stearothermophilus 16S ribosomal RNA. - Van Charldorp, R (1981)
The sequence and the position of post-transcriptionally modified residues of the 3' -terminal end of Bacillus stearothermophilus 16S ribosomal RNA have been determined from the fragment that is cleaved off by bacteriocin treatment. The fragment contains 52 nucleotides, as compared to the 49 nucleotides of the corresponding fragment from E. coli ribosomes, The additional nucleotides are present in the sequence UCU very next to the 3' -terminus as was published earlier (1). The remainder of the sequence is identical to the one of E. coli except at six positions, due to the UV melting properties of the colicin fragment from B. stearothermophilus in comparison to the same fragment of E. coli show that the RNA from the thermophile has a more stable secondary structure.